Simple synthesis of Cu2O/Na-bentonite composites and their excellent photocatalytic properties in treating methyl orange solution. Issue 5 (April 2016) - Li, Nai; Yang, Bujun; Xu, Lianchi; Xu, Gaojin; Sun, Wu; Yu, Shaoming
Abstract: Cu2 O/Na-bentonite (Cu2 O/NB) composites were firstly synthesized by a simple deposition method. The morphology and composition of the prepared catalysts were characterized by X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), Fourier transform infrared (FT-IR) spectroscopy, Brunauer–Emmett–Teller (BET) specific surface area. The results show that the Cu2 O microparticles can be immobilized on the surface of the NB. Visible-light photocatalytic properties of the Cu2 O/NB composites were evaluated using methyl orange (MO) as a model pollutant and the effects of various experimental factors on MO decolorization were investigated. Cu2 O/NB composites demonstrated a much higher photocatalytic activity than the pure Cu2 O particles under similar experimental conditions.